Leukocytosis and thrombocytopenia in pre-partum, post-partum cases and non-pregnant women: Leukocytosis and thrombocytopenia in pre-partum, post-partum cases and non-pregnant women - Akhter, Afia; Saleem, Fatima; Jehanzeb, Mian Muhammad; Mubarak , Bushra; Waheed, Kainat; Munir, Iqra; Saadullah, Marya; Anwar, Masooma (Pakistan BioMedical Journal, 2022)
Thrombocytopenia is a serious condition that may cause fatal outcomes for both mother and infant, whereas leukocytosis is an essential mediator of the inflammatory process and a marker for infection during pregnancy. Objective: The aim of the study was to compare the frequency of thrombocytopenia and leukocytosis among pre-partum, post-partum cases and non-pregnant healthy controls. Methods: Total 600 samples were collected and categorized into three groups, pre-partum, post-partum and non-pregnant 200 in each. From selected groups 3-5 ml blood was collected in EDTA tube and Sodium Citrate vial. Platelets, WBCs, RBCs and Hemoglobin levels were analyzed on Sysmex KX-21. PT and APTT of all samples was performed manually. Results: Leukocytosis was detected in 60% pre-partum and 64% post-partum, there was not statistically significant difference (p=0.596). In pregnant and non-pregnant, there was significant difference statistically (p<0.05). Thrombocytopenia was detected in 11% pre-partum, 13% post-partum cases and there was no statistical difference (p>0.05). There was statistical difference in frequency of thrombocytopenia between pregnant and non-pregnant women (p=0.03). There was no statistically significant difference in PT and APTT between pre-partum and post-partum (p>0.05). APTT were significantly different between pregnant and non-pregnant cases (p<0.05). Conclusion: The study concluded that leukocytosis and thrombocytopenia was found in higher frequency among pregnant women than non-pregnant women but there was no significant difference in frequency of leukocytosis and thrombocytopenia between pre-partum and post-partum women